2022
DOI: 10.1101/2022.01.19.22269564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole-exome Sequencing Study of Hypospadias

Abstract: While hypospadias is one of the most common male congenital disorders, the missing heritability contributed by rare variants with larger effects is poorly understood. To systematically explore the variant patterns in the developing of hypospadias, we performed whole exome sequencing (WES) in 191 severe hypospadias cohort and three trios. Subsequent RNA sequencing of 12 severe hypospadiac foreskins and 6 non-hypospadiac foreskins were conducted. Among previous reported hypospadias risk associated genes, we foun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Moreover, damaging variants of ciliary genes were found to be enriched in patients with transposition of the great arteries (TGA) (13), a complex congenital heart defect. Chen et al reported that knockout of the Dnah8 gene causing hypospadias resulted in decreased testosterone levels in male mice and failure to produce offspring (14). These results further substantiate the established link between ciliary function and CHD, hypospadias, and infertility.…”
Section: Wwwbiosciencetrendscom Bioscience Trends Advance Publication P3mentioning
confidence: 57%
“…Moreover, damaging variants of ciliary genes were found to be enriched in patients with transposition of the great arteries (TGA) (13), a complex congenital heart defect. Chen et al reported that knockout of the Dnah8 gene causing hypospadias resulted in decreased testosterone levels in male mice and failure to produce offspring (14). These results further substantiate the established link between ciliary function and CHD, hypospadias, and infertility.…”
Section: Wwwbiosciencetrendscom Bioscience Trends Advance Publication P3mentioning
confidence: 57%
“…We proposed that genetic contribution to PAIS is heavily concentrated in genes related to androgen-AR signaling or AR-centered network that are transcribed or expressed in relevant tissues. Rare damaging variants are likely to be causative than other classes of variants and hence explain some of the unknown genetic causes of birth defects, such as hypospadias (48,49). Furthermore, new genomic approaches for identifying non-coding, mosaic, structural or epigenetic variants will improve the understanding of the molecular causes (50).…”
Section: Discussionmentioning
confidence: 99%
“…Disruptions in the process of tubulization are associated with disturbances in the androgen signaling pathway. Genetic variations in the androgen signaling pathway can affect the development of the urethra, such as the formation of hypospadias (21). Unlike males, in female fetuses, the urethral sulcus remains open to form the vestibule due to the low levels of testosterone.…”
Section: Embryology and Etiologymentioning
confidence: 99%